BENTUK PENGEMBANGAN KEMAMPUAN SOSIAL EMOSIONAL PADA ANAK USIA DINI BERBASIS LOCAL WISDOM DI TK MUSLIMAT NU 089 KEPATIHAN PONOROGO - Arkam, Rohmad; Molyono, Molyono (Prodi PG-PAUD, FKIP, Universitas Trilogi, 2021)
Abstract: This research is motivated by the form of developing emotional social abilities in early childhood based on local wisdom (local wisdom) at Muslimat NU Kindergarten 089 Kepatihan Ponorogo. The research used in this research is to use a type of field case study with qualitative research. Aimed at seeing forms of developing emotional social abilities in young children based on local wisdom (local wisdom) at TK Muslimat NU 089 Kepatihan Ponorogo. The subjects in this study were students of grade A and B Muslimat kindergarten NU 089 Kepatihan Ponorogo. The informants of this study were the principal and teacher of TK Muslimat NU 089 Kepatihan Ponorogo. Data collection uses observation, interviews, and documentation. Based on data analysis in the field, local wisdom forms the basis of emotional emotional development in NU 089 Muslimat Kindergarten Ponorogo in the form of dolanan songs, very appropriate for developing social emotional aspects of children, because in learning there is acomprehensive reaction from all classroom level environments.